PROUNI: avaliação das contribuições do Programa para a Educação Superior na perspectiva de alunos contemplados pelo programa na cidade de Fortaleza-Ceará - Oliveira, Patrícia Alves de (2017)
This dissertation is related to the line of research Public Policies and Social Changes of the Professional Masters in Public Policy Evaluation of the Federal University of Ceará. The objective Prouni: Evaluation of the contributions of the program for Higher Education from the perspective of students contemplated by the program in the city of Fortaleza-Ceará is to be able to have a critical understanding of this program of government and what change has caused in the life of Many students in which the family has low income in Brazil. The main theme of the work revolves around PROUNI, which was created in 2005 under the government of Luís Inácio Lula da Silva, and showed the whole course for the creation of the program, in addition to the requirements for the student to be considered. The issues of democratization of access to education and social inclusion were also addressed. This is a qualitative study, in which we sought to interview health students studying at a private university in 2016, with the help of PROUNI. In the methodology, we tried to use Bardin (2010) to categorize the interviews. As data analysis we could identify that without the program they would not be able to attend a college and that they had many expectations regarding a future with greater financial conditions and better quality of life. The study gave us grounding to verify that the evaluated program does not meet all the requirements to democratize the access to the whole higher education and to cause the social inclusion of less favored people, because it presents some flaws, it needs to offer the conditions of the student to remain in the faculty, Because it does not receive a cost aid for the expenses during the course of the course.